2018
DOI: 10.1080/23320885.2018.1489250
|View full text |Cite
|
Sign up to set email alerts
|

Management of second metacarpal chronic osteomyelitis by induced membrane technique

Abstract: Management of chronic osteoarticular infection of the hand is a true challenge. Several methods of treatment are described in the literature to eradicate the infection. We present a case in which chronic osteomyelitis of the second metacarpal was treated by induced membrane technique, with successful outcome and complete hand recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this report, a four-week interval was used between cement spacing and bone graft for early rehabilitation and decreased burden on the patient [3]. However, Tabib et al reported on the treatment of chronic osteomyelitis of the second metacarpal following treatment of a Bennett fracture via the induced membrane technique with an eight-week interval between stages and successful bony union [6]. Compared to our case, the previous two reports were not for traumatic segmental bone loss and did not utilize a temporary antibiotic cement spacer as described in this report.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this report, a four-week interval was used between cement spacing and bone graft for early rehabilitation and decreased burden on the patient [3]. However, Tabib et al reported on the treatment of chronic osteomyelitis of the second metacarpal following treatment of a Bennett fracture via the induced membrane technique with an eight-week interval between stages and successful bony union [6]. Compared to our case, the previous two reports were not for traumatic segmental bone loss and did not utilize a temporary antibiotic cement spacer as described in this report.…”
Section: Discussionmentioning
confidence: 96%
“…Despite its prevalence in the lower extremities, case reports and series on the successful use of the Masquelet technique are also described in the upper extremity. These studies have described its use in treating bone loss secondary to trauma, osteomyelitis, or nonunion, as well as for arthrodesis or septic arthritis [3][4][5][6][7][8][9]. In this article, we present the case of a patient who sustained a gunshot wound resulting in traumatic bone loss, articular surface destruction, and subsequent osteomyelitis following initial treatment, and ultimately underwent the Masquelet procedure with successful arthrodesis of the distal interphalangeal (DIP) joint as an alternative to digit amputation.…”
Section: Introductionmentioning
confidence: 99%
“…After two to three months, complete bone healing was achieved in all cases. Additionally, a case was described of a patient treated with the masquelet technique, with a metacarpal I fracture and osteomyelitis secondary to surgical fracture treatment [ 4 ]. The cement spacer was removed after eight weeks; the remaining defect filled with cancellous bone and stabilized with a plate.…”
Section: Considerationsmentioning
confidence: 99%